34. BURNOUT SYNDROME AMONG PEDIATRIC NURSES AND RELATED FACTORS (Vietnam Journal of Community Medicine, 2025)
Objectives: This study aimed to determine the prevalence of occupational burnout and associated factors among pediatric nurses working in clinical departments at Children's Hospital 2.Methods: A cross-sectional descriptive design was employed. The Maslach Burnout Inventory – Human Services Survey (MBI-HSS) was used to assess three dimensions of burnout: emotional exhaustion (EE), depersonalization (DP), and reduced personal accomplishment (PA). Work environment-related factors were evaluated using the Areas of Worklife Survey (AWS).Results: Among 226 nurses surveyed, the prevalence of moderate to high burnout was 44.2% for EE, 17.3% for DP, and 23.9% for PA. The mean scores for each domain were: EE 2.26 ± 1.52; DP 1.09 ± 1.15; and PA 4.63 ± 0.92. Statistically significant factors associated with burnout included: hospital income, night shift frequency, weekend overtime, additional work outside the hospital, workload, perceived fairness, sense of community, recognition, and professional values (p < 0.05).Conclusion: A considerable level of occupational burnout was observed among pediatric nurses, particularly in the domain of emotional exhaustion. There is an urgent need to implement supportive policies to improve the working environment, enhance mental well-being, and ultimately improve the quality of pediatric patient care.
Keywords: Occupational burnout, emotional exhaustion (EE), depersonalization (DP), personal accomplishment (PA), pediatric nurse, MBI-HSS, Children's Hospital 2.